Jamur Mikoriza Vesikular Arbuskular (MVA) Pada Tiga Jenis Tanah Rhizosfer Tumbuhan Lakum (Cayratia trifolia (L.) Domin) - Mukarlina, Tri Oktarini Adiaty Riza Linda (Universitas Tanjungpura, 2018)
The lakum plant (Cayratia trifolia (L.) Domin) is a wild plant so it is easily found in various types of soil, such as alluvial soil, ultisol soil and soil with salinity (saline soil). The ability of the lakum plant (C. trifolia) to grow on alluvial soil, ultisol soil, and saline soils is presumably cause by a role of Vesicular Arbuscular Mycorrhizal (VAM) fungi. This research aims to find out about VAM fungi in the rhizosphere of the lakum plant (C. trifolia) and the rate of VAM fungal infection in three types of rhizosphere soil of the lakum plant. This research was conducted for three months, starting from January to May 2018 at the Microbiology Laboratory of the Faculty of Mathematics and Natural Sciences of Tanjungpura University. The research procedure included several stages, namely sampling, isolation of spores by a combination of wet filter pouring technique, identification and characterization, and coloring and making root preparations with coloring method. Based on the results of the research, the spores of the VAM fungi found in alluvial soil consisted of the genera Acaulospora, Archaeospora, Glomus and Paraglomus. The spores of the genus of VAM fungi found on the saline soil were only the genus Glomus. The spores of the genus of VAM fungi found on ultisol soil consisted of the genera Acaulospora, Glomus and Paraglomus. The results of observations show that VAM fungal infection in alluvial soil was 25% (low), in saline soil 50.6% (high) and ultisol soil 53% (high)